Avaliação do desenvolvimento da atriplex nummularia lind. submetida à irrigação com água salina e ao fungo micorrízico arbuscular. - Melo, Camila Freire de (2019)
The semiarid Pernambuco exhibits climate vulnerability, which in turn promotes environmental and social damage to a locality. With this, a search for alternatives of low cost and high efficiency that are adapted to the characteristics of the environment are constant. Therefore, the work is better than the effect of the association of mycorrhizal fungi with desalinizer residue on the development of Atriplex nummularia. The experiment was carried out in a greenhouse at the Instituto Agronômico de Pernambuco - IPA, Recife, Pernambuco, Brazil, with 5 days of rejection with the addition of sodium chloride and without arbuscular mycorrhizal fungi (AMF) with and without nutrient solution. The experimental design was a randomized block design, with two replicates, totaling 80 experimental units. To evaluate the yield of Atriplex cultivar, the following variables are: plant height, specific element contents, copious and root colonization. A soil sample, too, was collected for complete chemical analysis. The obtained data were submitted to the individual and joint statistical analysis of the studied variables with a test variance by the F test as averages compared by the Tukey test at 5% probability. Identity and methods of nutritive analysis in the same as FMA and the nutritive solution. The absorption of sodium, potassium, calcium, magnesium and nitrogen was more favored in the treatments with non-autoclaved soil. The positive correlation of height with mycorrhizal colonization was observed in the T4 treatment (in the absence of 21 g NaCl) in the presence of AMF in the non-autoclaved soil. Therefore, mycorrhizal colonization in Atriplex numularia and positive with a ratio (R = 0.90 per level of p <0.05) may be a presence of microorganisms that favor genetic mutuality, favoring its growth as high extractions of Na (22%) and Mg (20%) by the plant, evidencing a potential of the use of the protein in phytoextraction programs in soils affected by salts.